2021
DOI: 10.3390/cancers13215339
|View full text |Cite
|
Sign up to set email alerts
|

Germline Predisposition to Pediatric Cancer, from Next Generation Sequencing to Medical Care

Abstract: Knowledge about genetic predisposition to pediatric cancer is constantly expanding. The categorization and clinical management of the best-known syndromes has been refined over the years. Meanwhile, new genes for pediatric cancer susceptibility are discovered every year. Our current work shares the results of genetically studying the germline of 170 pediatric patients diagnosed with cancer. Patients were prospectively recruited and studied using a custom panel, OncoNano V2. The well-categorized predisposing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Knowledge about the prevalence of CPSs in children presenting with malignancy is critical to appropriately designing the optimal pathway to screen this population. The proportion of childhood cancer secondary to germline genetic predisposition, which was estimated to be around 4% in the ‘90s [ 14 ], grew to approximately 10% in broad sequencing studies performed in the last 10 years, probably due to the identification of previously unrecognized CPSs and the advancement of the available technologies for genetic sequencing [ 3 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 ]. The 10 main studies analyzing the prevalence of CPS-associated variants in children and adolescents diagnosed with cancer are shown in Table 1 .…”
Section: Prevalence Of Monogenic Cancer Predisposition Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about the prevalence of CPSs in children presenting with malignancy is critical to appropriately designing the optimal pathway to screen this population. The proportion of childhood cancer secondary to germline genetic predisposition, which was estimated to be around 4% in the ‘90s [ 14 ], grew to approximately 10% in broad sequencing studies performed in the last 10 years, probably due to the identification of previously unrecognized CPSs and the advancement of the available technologies for genetic sequencing [ 3 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 ]. The 10 main studies analyzing the prevalence of CPS-associated variants in children and adolescents diagnosed with cancer are shown in Table 1 .…”
Section: Prevalence Of Monogenic Cancer Predisposition Syndromesmentioning
confidence: 99%
“…Interestingly, this proportion did not vary substantially among different studies even if performed in diverse populations and settings. Important exceptions characterized by a lower diagnostic yield are the cohorts described by Wang et al [ 15 ] and the cohort described by Von Stedingk et al [ 19 ]. The study by Wang included 3006 childhood cancer survivors, showing only a 5.8% prevalence of pathogenic or likely pathogenic variants (PV or LPV) for CPSs.…”
Section: Prevalence Of Monogenic Cancer Predisposition Syndromesmentioning
confidence: 99%
“…Specific features which should be taken into consideration are congenital anomalies, facial dysmorphisms, intellectual disability, aberrant growth, skin anomalies, haematological disorders, and immune deficiency. Gargallo et al evaluated Jongmans et al’s tool in relation to pathogenic mutations and found a sensitivity of 94% and a specificity of 77% in their cohort [ 3 ]. Jongmans et al’s criteria modification by Ripperger et al (with an added category of genetic tumour analysis which may reveal a defect suggesting a germline predisposition and expanded list of cancer types associated with CPS, presented in Figure 1 ) was found to have 100% sensitivity in this cohort [ 3 , 101 ].…”
Section: The Importance Of Identifying Genetic Predispositions To Pae...mentioning
confidence: 99%
“…Gargallo et al evaluated Jongmans et al’s tool in relation to pathogenic mutations and found a sensitivity of 94% and a specificity of 77% in their cohort [ 3 ]. Jongmans et al’s criteria modification by Ripperger et al (with an added category of genetic tumour analysis which may reveal a defect suggesting a germline predisposition and expanded list of cancer types associated with CPS, presented in Figure 1 ) was found to have 100% sensitivity in this cohort [ 3 , 101 ]. Schwermer et al also reported a significant impact of the CPS questionnaire on diagnosis improvement.…”
Section: The Importance Of Identifying Genetic Predispositions To Pae...mentioning
confidence: 99%
See 1 more Smart Citation